Between Ambition and Quietism: the Socio-political Background of 1 Thessalonians 4,9-12 - Rulmu, Callia (Biblica, 2010)
Assuming the Christian group of Thessalonica to be a professional voluntary association of hand-workers (probably leatherworkers), this paper argues that 1 Thessalonians in general, and especially the injunction to «keep quiet» (4,11), indicates Paul’s apprehension regarding how Roman rulers, city dwellers, and Greek oligarchies would perceive an association converted to an exclusive cult and eager to actively participate in the redistribution of the city resources. Paul, concerned about a definite practical situation rather than a philosophically or even theologically determined attitude, delivered precise counsel to the Thessalonians to take a stance of political quietism as a survival strategy.